Red blood cell count in cerebrospinal fluid was correlated with inflammatory markers on the seventh postoperative day and all associated with the outcome of aneurysmal subarachnoid hemorrhage patients - Min, Jie; Zhao, Yongfeng; Lv, Chenxi; Hu, Hang (Frontiers in Medicine, 2024)
Background: Exploring factors associated with the outcome of patients with aneurysmal subarachnoid hemorrhage (aSAH) has become a hot focus in research. We sought to investigate the associations of inflammatory markers and blood cell count in cerebrospinal fluid with the outcome of aSAH patients.We carried a retrospective study including 200 patients with aSAH and surgeries. The associations of neutrophil, lymphocyte, neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), systemic immune inflammation index (SII), system inflammation response index (SIRI), and blood cell count in cerebrospinal fluid on the 1st and 7th postoperative days with the outcome of aSAH patients were investigated by univariate analysis and multivariate logistic regression model.Results: According to the modified Rankin scale (mRS) score, there were 147 patients with good outcome and 53 patients with poor outcome. The neutrophil, NLR, SIRI, and SII levels on the seventh postoperative day in patients with poor outcome were all significantly higher than patients with good outcome, P < 0.05. The multivariate logistic regression model including inflammatory markers and blood cell counts in cerebrospinal fluid on the 1st postoperative day confirmed that red blood cell count in cerebrospinal fluid (≥177 × 10 9 /L) (OR: 7.227, 95% CI: 1.160-45.050, P = 0.034) was possibly associated with poor outcome of aSAH patients, surgical duration (≥169 minutes), Fisher grade (III-IV), hypertension, and infections were also possibly associated with the poor outcome. The model including inflammatory markers and blood cell counts in cerebrospinal fluid on the 7th postoperative day confirmed that red blood cell count in cerebrospinal fluid (≥54 × 10 9 /L) (OR: 39.787, 95% CI: 6.799-232.836, P < 0.001) and neutrophil-lymphocyte ratio (≥8.16) (OR: 6.362, 95% CI: 1.424-28.428, P = 0.015) were all possibly associated with poor outcome of aSAH patients. The NLR (r=0.297, P = 0.007) and SIRI (r=0.325, P = 0.003) levels were all correlated with the count of red blood cells in cerebrospinal fluid.Discussion: Higher neutrophil-lymphocyte ratio and higher red blood cell count in cerebrospinal fluid were all possibly associated with poor outcome of patients with aneurysmal subarachnoid hemorrhage. However, we need a larger sample study.